Characteristics of short REM sleepers and long-term CPAP use in the RICCADSA cohort - Balcan, Baran; Celik, Yeliz; Strollo, Patrick J.; Peker, Yuksel (Sleep Medicine, 2025)
Study objectives: The impact of rapid eye movement (REM) sleep duration on long-term adherence to continuous positive airway pressure (CPAP) therapy in patients with obstructive sleep apnea (OSA) is unclear. This study aimed to assess the characteristics of individuals with short REM sleep and investigate whether reduced REM sleep is associated with lower CPAP adherence over a two-year period in the RICCADSA cohort. Methods: This secondary analysis included participants from the RICCADSA trial who had total sleep time of at least 240 min on baseline polysomnography and available CPAP adherence data for two years. Participants were categorized into short REM sleep (<30 min) and normal REM sleep (≥30 min) groups. Sleep parameters, clinical characteristics, and CPAP adherence data were analyzed. Results: Among 253 participants, 52 (20.6 %) had short REM sleep. The short REM sleep group was older (66.8 vs. 63.0 years, p = 0.002), had a higher prevalence of obesity (48.1 % vs. 31.3 %, p = 0.024), underwent more frequent coronary artery bypass grafting (38.5 % vs. 22.4 %, p = 0.018), and had higher rates of anxiety (33.3 % vs. 16.4 %, p = 0.007). They exhibited shorter total sleep time, longer sleep onset latency, reduced sleep efficiency, and more severe OSA (AHI: 56.7 vs. 31.4 events/h, p < 0.001). Regression analysis revealed that short REM sleep was significantly associated with lower CPAP adherence at two years (β = −0.15, 95 % CI: 1.92 to −0.09, p = 0.031). Conclusions: Short REM sleep is associated with older age, obesity, higher anxiety levels, and more severe OSA. Importantly, it is linked to lower long-term CPAP adherence, underscoring the need to identify and support this subgroup to improve treatment outcomes. Clinical registration: The study was registered at the national research website in Sweden through the database of the Skaraborg Hospital (nr VGSKAS-4731; 04.29.2005) as well as with ClinicalTrials.gov, number NCT00519597.
Publisher Copyright: © 2025
Keywords: CPAP adherence; Obstructive sleep apnea; REM sleep